Bilateral deficit in countermovement jump and its association with change of direction performance in basketball and tennis players - Kozinc, Ž.; Sarabon, N. (Sports Biomechanics, 2021)
The purpose of this study was to assess the association between bilateral deficit (BLD) in countermovement jump and change of direction (CoD) performance. Therefore, 165 young basketball players (60 females) and 95 young tennis players (39 females) performed two different CoD tasks (90° and 180° turns) and bilateral and unilateral countermovement jumps. BLD was calculated based on jump height, peak power and several phase-specific force impulses (FI). For male athletes, several statistically significant small to moderate associations were found between the CoD performance and BLD (0.21-0.52). While the BLD in the propulsive phase FI seems to be most consistently associated with CoD performance, all associations were weak (0.21-0.28 in basketball, 0.28-0.36 in tennis). Associations between BLD in total positive (braking and propulsive phase) FI and CoD performance were moderate (0.45-0.52) in male tennis players. For female athletes, the associations were even smaller and almost exclusively statistically non-significant. Although indirectly, our results imply that resistance training based on unilateral exercises could be useful to improve CoD performance. It has to be stressed that further training studies are needed to directly confirm this assumption.